Empowering Teachers to Shape Intelligent Children with Local Character Through Green-School-Based Strategies: A Multi-Case Study in Kindergarten - Ratna Purwanti; Ahmad Suriansyah; Ahmad Alim Bachri; Noorhapizah Noorhapizah (Vidya Karya, 2026)
The importance of a leader in empowering others to achieve goals optimally, especially in forming intelligent children with local character in early childhood education, is still limited. Therefore, this study aims to describe teacher empowerment strategies in shaping intelligent children with local character through a green school approach. This study utilizes a qualitative method with a multi-case design. Data collection techniques include in-depth interviews, observations, and document analysis. The validity of the findings is credibility, transferability, dependability, and confirmability. Data analysis utilizes an interactive model from Miles and Huberman (2014): data collection, data condensation, data presentation, and data conclusion. The results of the study showed that leadership values and beliefs, such as religious values, local character values, exemplary values, and collegiality values , are fundamental in implementing teacher empowerment strategies to shape intelligent children with local character. including improvement (mentoring; competency improvement-based digitalization); nurturing (providing work motivation; individual involvement in work teams; involving all teachers based on their competencies); maintenance (providing freedom to innovate; creating positive work culture; and creating work climate with a sense of family); protecting (building positive communication; and providing recognition); and integrated into learning to form the local character of early childhood accompanied by monitoring and evaluation both internally and externally. The results of this study can be used as a reference and consideration in developing a principle in empowering others.